Sleep Quality and Its Relationship with Temporomandibular Symptoms in Adolescents: A Cross-Sectional Study - Saha, Dr. Ankit; Iqbal, Dr. Haider; D S, Dr. Pramod; Hegde, Dr. Shipha; Arya, Dr. Ashtha; Mishra, Dr. Silpi ranjan (Adolescência e Saúde, 2026)
Background: Temporomandibular disorders (TMD) represent a significant health concern among adolescents, potentially impacting quality of life and daily functioning. Sleep quality has emerged as a modifiable factor that may influence musculoskeletal pain conditions, yet its relationship with temporomandibular symptoms in the adolescent population remains underexplored. Methods: A cross-sectional study was conducted among 472 adolescents (mean age: 15.0 ± 1.7 years; 52.8% female) enrolled in secondary schools. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while temporomandibular symptoms were evaluated using the Fonseca Anamnestic Index (FAI). Demographic and behavioral variables were collected through a structured questionnaire. Statistical analyses included descriptive statistics, chi-square tests, Pearson correlation coefficients, and multiple logistic regression. Results: Poor sleep quality (PSQI > 5) was observed in 40.3% of participants, while 35.6% presented with at least mild TMD symptoms. A significant positive correlation was found between PSQI scores and FAI scores (r = 0.376, p < 0.001). Adolescents with poor sleep quality demonstrated 2.48 times higher odds of presenting TMD symptoms compared to good sleepers (95% CI: 1.69-3.64, p < 0.001). Female sex, excessive screen time, and psychological stress were identified as additional significant predictors. Conclusion: Poor sleep quality is significantly associated with increased temporomandibular symptoms in adolescents. These findings suggest that sleep assessment should be incorporated into the clinical evaluation of adolescents presenting with TMD symptoms, and sleep hygiene interventions may serve as an adjunctive therapeutic strategy.